Kualitas Pelayanan Terhadap Word Of Mouth Dengan Kepuasan Pelanggan Sebagai Variabel Intervening Pada Holaa Cafe Gresik - Wahyudi, Muhammad Zaki; Setiyarini, Triana (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
The objectives of this study are to explain (1) the significant influence of service quality on customer satisfaction; (2) the significant influence of customer satisfaction on word of mouth; (3) the significant influence of service quality on word of mouth; (4) the presence of an indirect effect between service quality on word of mouth with customer satisfaction as an intervening variable. The method used in this research is causal research with a quantitative approach. Data collection techniques were conducted through questionnaires. The sample was taken using the Lemeshow formula because the population size was unknown, and the sample taken at Holaa Café amounted to 100 samples. Data analysis in this study used the SPSS application. The results of this research indicate (1) the significant positive influence of service quality on customer satisfaction; (2) the significant positive influence of service quality on word of mouth; (3) the significant positive influence of customer satisfaction on word of mouth; (4) the influence of service quality on word of mouth, seen from the regression coefficient level, is greater than the indirect influence between service quality on word of mouth with customer satisfaction as an intervening variable. Thus, it can be concluded that the presence of an intervening variable (customer satisfaction) makes the level of influence between service quality on word of mouth lower.